2021
DOI: 10.1093/gbe/evab015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spread of Mutant Alleles in Worldwide SARS-CoV-2 Strains Revealed by Genome-Wide Single Nucleotide Polymorphism and Variation Analysis

Abstract: The novel coronavirus (SARS-CoV-2) has become a pandemic and is threatening human health globally. Here, we report 9 newly evolved SARS-CoV-2 single nucleotide polymorphism (SNP) alleles those underwent a rapid increase (7 cases) or decrease (2 cases) in their frequency for 30% ∼ 80% in the initial four months, which are further confirmed by intra-host single nucleotide variation (iSNV) analysis using raw sequence data including 8217 samples. The 9 SNPs are mostly (8/9) located in the coding region and are mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 50 publications
(61 reference statements)
2
36
0
Order By: Relevance
“…These results demonstrated that the R203K/G204R mutation enhanced viral replication through increasing virion infectivity in primary human upper airway tissues. In consistent to our experimental results, we previously observed a negative correlation of R203/G204 IF with the cycle threshold for positive signal in E gene-based RT-PCR (Ct) 10 .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results demonstrated that the R203K/G204R mutation enhanced viral replication through increasing virion infectivity in primary human upper airway tissues. In consistent to our experimental results, we previously observed a negative correlation of R203/G204 IF with the cycle threshold for positive signal in E gene-based RT-PCR (Ct) 10 .…”
Section: Resultssupporting
confidence: 92%
“…The increase in replication may lead to the increase of virulence and fitness in the end. Other high infectivity related mutations, such as D614G and N510Y, also showed association with the increased fitness and severity of diseases 9,10,3335 . R203K/G204R is akin to predominance like D614G (Figure 1) and is shared by rapidly growing lineages, B.1.1.7 and P.1.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations